Chemotherapeutic Stress Induces Transdifferentiation of Glioblastoma Cells to Endothelial Cells and Promotes Vascular Mimicry. (18th June 2019) - Baisiwala, Shivani; Auffinger, Brenda; Caragher, Seamus P.; Shireman, Jack M.; Ahsan, Riasat; Lee, Gina; Hasan, Tanwir; Park, Cheol; Saathoff, Miranda R.; Christensen, Anne C.; Ahmed, Atique U.
Abstract : Glioblastoma (GBM) is the most common and aggressive primary malignant brain tumor affecting adults, with a median survival of approximately 21 months. One key factor underlying the limited efficacy of current treatment modalities is the remarkable plasticity exhibited by GBM cells, which allows them to effectively adapt to changes induced by anticancer therapeutics. Moreover, GBM tumors are highly vascularized with aberrant vessels that complicate the delivery of antitumor agents. Recent research has demonstrated that GBM cells have the ability to transdifferentiate into endothelial cells (ECs), illustrating that GBM cells may use plasticity in concert with vascularization leading to the creation of tumor-derived blood vessels. The mechanism behind this transdifferentiation, however, remains unclear. Here, we show that treatment with temozolomide (TMZ) chemotherapy induces time-dependent expression of markers for glioma stem cells (GSCs) and immature and mature ECs. In addition, GBM tumors growing as orthotopic xenografts in nude mice showed increased expression of GSC and EC markers after TMZ treatment. Ex vivo FACS analysis showed the presence of immature and mature EC populations. Furthermore, immunofluorescence analysis revealed increased tumor-derived vessels in TMZ-recurrent tumors. Overall, this study identifies chemotherapeutic stress as a new driver of transdifferentiation of tumor cells to endothelial cells and highlights cellular plasticity as a key player in therapeutic resistance and tumor recurrence.